The Böhler’s angle in population of central Serbia – a radiological study - Živanović-Mačužić, Ivana; Vulović, Maja; Vojinović, Radiša; Jovanović, Milan; Radunović, Aleksandar; Cvetković, Aleksandar; Stojiljković, Miloš; Milošević, Bojan; Ivošević, Anita; Aksić, Milan; Simović, Aleksandra; Jeremić, Dejan (Vojnosanitetski pregled, 2020)
Background/Aim. The values of the Böhler’s angle (BA) are relevant parameters for diagnosis, management and prognosis of the calcaneal fracture and the outcome. Range of normal values of Böhler’s angle (BA) in adults varies depending on the examined population, age, gender or ethnicity. The aim of this study was to determine the range of normal values of the Böhler’s angle in the central part of Serbia. Methods. The lateral foot radiographs of 225 subjects (111 males and 114 females) without calcaneal fractures, divided into 6 age groups were observed to determine the normal values of the Böhler’s angle by using the IMPAX 6.5.2.114 Enterprise software. Obtained values for Böhler’s angle were compared among gender and groups using appropriate statistical tests. Results. The mean of Böhler’s angle in observed population was 34.06°, ranging from 25.1° to 49.5° and was higher in males than in females included in our study. Gender difference was statistically significant. The distribution of the mean BA across the age groups showed tendency of decreasing with age and the highest BA was found in the youngest group. Conclusion. The findings presented in this paper confirmed the existence of wide range of BA values as well as its gender and age differences.